Challenges in the Practice of Sexual Medicine in the Time of COVID-19 in China. Issue 7 (28th April 2020) - Li, Weiran; Li, Guanjian; Xin, Cong; Wang, Yaochi; Yang, Sen
Abstract: Background: In March 2020, the World Health Organization declared coronavirus disease 2019 (COVID-19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a pandemic. Currently, data on changes in sexual behavior during the COVID-19 outbreak are limited. Aim: The present study aimed to obtain a preliminary understanding of the changes in people's sexual behavior, as a result of the pandemic, and explore the context in which they manifest. Methods: A convenience sample of 270 men and 189 women who completed an online survey consisting of 12 items plus an additional question were included in the study. Outcomes: The study outcomes were obtained using a study-specific questionnaire to assess the changes in people's sexual behavior. Results: While there was a wide range of individual responses, our results showed that 44% of participants reported a decrease in the number of sexual partners and about 37% of participants reported a decrease in sexual frequency. Multiple regression analysis showed that age, partner relationship, and sexual desire were closely related to sexual frequency. In addition, we found that most individuals with risky sexual experiences had a rapid reduction in risky sexual behavior. Clinical Implications: The current findings contribute to identifying another potential health implication associated with the COVID-19 pandemic and report preliminary evidence of the need to provide potential interventions for the population. Strength & Limitations: This study is the first to perform a preliminary exploration of sexual behavior during the COVID-19 outbreak. The generalizability of the results is limited, given that only a small convenience sample was used. Conclusion: During the height of the COVID-19 outbreak, overall sexual activity, frequency, and risky behaviors declined significantly among young men and women in China.